La participación ciudadana en el presupuesto participativo del Gobierno Autónomo Descentralizado del cantón Tosagua provincia de Manabí año 2019 - Durán Rodríguez, Jhon Fernando (2022)
Currently, citizen intervention is a right established by the Constitution of Ecuador so that the entire population, individually and collectively, is involved in matters of public interest. Under this approach, the objective of the research is to evaluate the management of citizen participation in the participatory budget of the Decentralized Autonomous Government of the Tosagua canton, province of Manabí, year 2019. The methodology used included a comparative table that allowed linking the laws that govern the mechanism. participation of the citizens, then an interview was applied to a GAD official, where it was possible to know the current situation that exists regarding the object of study. Subsequently, a survey was applied to 381 people whose main results showed that 59% of respondents revealed that citizen participation is a right, therefore, their opinions should be respected in relation to a specific topic, 88% said that it is It is important that they be involved more directly in the participatory budget, on the other hand, with 32%, the users stated that they do know about the municipal ordinance that the GAD has. For this reason, it is concluded that; the proposed strategies are of great support which effectively contribute to the common welfare of the entire canton, the same that was socialized and welcomed positively by the authorities.